A case study on the classification of somersault jumping motion characteristics in trampoline gymnasts using the TJ-index - Matsushima, M. (Sports Biomechanics, 2025)
The purpose of this study was to propose the TJ-index, which uses deflection distance and contact time as variables, as an index of somersault jumps in trampoline competitions, and to clarify the characteristics of the jumping motion of trampoline gymnasts as a case study. Ten participants, ranging from elite trampoline gymnasts to those at the national competition level, performed 10 consecutive backward somersaults and forward somersault half-twists in alternating sequence. A strong positive correlation was observed between the TJ-index and time of flight (r = 0.98, p < 0.01). The relationship between deflection distance and contact time, which together constitute the TJ-index, was classified into six types using Ward`s cluster analysis method. Moreover, normalising deflection distance by body mass revealed individual jump characteristics. The bed`s deflection distance may primarily result from either the gymnast`s body mass or their active jumping motion. A strong negative correlation was observed between deflection distance per unit of body mass and contact time (r = -0.87, p < 0.01). These findings suggested the existence of body mass optimisation in trampoline gymnasts. The use of the TJ-index appears to have potential for identifying and classifying the jumping motion tendencies of trampoline gymnasts by type.